A Multi-Criteria Approach for Quantifying the Impact of Global Megatrends on the Pulp and Paper Industry: Insights into Digitalization, Social Behavior Change, and Sustainability - Keren A. Vivas; Ramon E. Vera; Sudipta Dasmohapatra; Ronald Marquez; Sophie Van Schoubroeck; Naycari Forfora; Antonio José Azuaje; Richard B. Phillips; Hasan Jameel; Jason A. Delborne; Daniel Saloni; Richard A. Venditti; et al. (Logistics)
Background: The pulp and paper industry (P&PI) is undergoing significant disruption driven by global megatrends that necessitate advanced tools for predicting future behavior and adapting strategies accordingly. Methods: This work utilizes a multi-criteria framework to quantify the effects of digitalization, changes in social behavior, and sustainability as three major megatrends transforming the P&PI industry, with a specific focus on hygiene tissue products. Thus, the research combines a comprehensive literature review, insights from a Delphi study, and topic modeling to qualitatively and quantitatively assess the present and future impacts of these global megatrends. Results: The findings suggest an urgent need to identify alternative raw materials to prevent potential supply chain disruptions. Moreover, due to shifts in social behavior, it becomes critical for businesses to substantiate their sustainability claims with hard data to avoid the risk of a “greenwashing” perception among consumers. Conclusions: This study provides decision support for strategic planning by highlighting actionable insights, quantitative predictions, and trend analysis, alongside the examination of consumer and market trends. It aims to incorporate diverse stakeholder perspectives and criteria into decision-making processes, thereby enriching the strategic planning and sustainability efforts within the P&PI industry.